2018
DOI: 10.1007/s00382-018-4081-y
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variability of the ENSO teleconnection to the wintertime North Pacific

Abstract: The El Niño/Southern Oscillation (ENSO) strongly influences the large-scale atmospheric circulation over the extratropical North Pacific during boreal winter, which has an important impact on North American winter climate. This study analyses the interdecadal variability of the ENSO teleconnection to the wintertime extratropical North Pacific, over the period 1900-2010, using a range of observationally derived datasets and an ensemble of atmospheric model simulations. The observed teleconnection strength is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 59 publications
1
25
0
3
Order By: Relevance
“…That means that regions which appear more predictable in the real world than in the model (i.e. paradoxical or underconfident) during recent decades, were strongly overconfident during the mid‐century decades (see also O'Reilly, ). In the earlier parts of the twentieth century the situation appears less extreme in either direction with slightly higher values of perfect model skill over Greenland and the northern North Atlantic and moderate observed skill levels over most of the North Atlantic except for the northeastern parts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That means that regions which appear more predictable in the real world than in the model (i.e. paradoxical or underconfident) during recent decades, were strongly overconfident during the mid‐century decades (see also O'Reilly, ). In the earlier parts of the twentieth century the situation appears less extreme in either direction with slightly higher values of perfect model skill over Greenland and the northern North Atlantic and moderate observed skill levels over most of the North Atlantic except for the northeastern parts.…”
Section: Discussionmentioning
confidence: 99%
“…Minobe, ; Hoerling et al, ; Derome et al, ; Fletcher and Saunders, ; Greatbatch and Jung, ; Douville et al, ; Hegerl et al, ; Huang et al, ) suggesting that such differences are indeed physically based. In particular, the temporal skill evolution of the NAO co‐varies with changes in the skill of the Pacific–North America (PNA) pattern that are highly statistically significant and relate to changes in the ENSO–North Pacific teleconnections (O'Reilly et al, ; O'Reilly, ). Further studies to understand the physical mechanisms of these inter‐decadal general circulation changes in the atmosphere and ocean both in observed data as well as in models (initialised and non‐initialised: Kumar and Chen, ) are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERA‐20C IC experiment is the hindcast that was performed by Weisheimer et al () over the entire twentieth century. They found that the skill of the NAO (as well as the Pacific/North American pattern) exhibited a minimum in the mid‐twentieth century, when there was relatively weak forcing from tropical Pacific SSTs (O'Reilly et al ; O'Reilly, ). The hindcast period analysed here primarily covers the later period where the ERA‐20C IC experiment exhibits higher levels of skill.…”
Section: Datasets Experiments and Methodsmentioning
confidence: 99%
“…) suggests that there is significant variation of over‐ and underconfidence during the 20th century linked to long‐term variability of the global circulation and teleconnections (e.g. O'Reilly, ). Analysis of a much longer set of seasonal forecasts such as that described in Weisheimer et al .…”
Section: Resultsmentioning
confidence: 99%